Does folic acid supplementation have a positive effect on improving memory? A systematic review and meta-analysis of randomized controlled trials - Akhgarjand, Camellia; Ebrahimi Mousavi, Sara; Kalantar, Zahra; Bagheri, Amir; Imani, Hossein; Rezvani, Hamid; Ghorbi, Mahmoud Dehghani; Vahabi, Zahra (Frontiers in Aging Neuroscience, 2022)
ABSTRACT The results of randomized controlled trials (RCTs) on the effect of folic acid supplementation on memory status due to various heterogeneity, dosage, duration, and cognitive function assessments were inconclusive. Therefore, we have performed a systematic review and meta-analysis to investigate the effect of folic acid supplementation on memory in RCTs. Comprehensive computerized systematic searches were conducted throughout Scopus, PubMed/Medline, and Google Scholar from inception until February 2022 to investigate the effect of folic acid supplementation memory levels in RCTs. The standardized mean difference (SMD) and 95% confidence interval (CIs) were used to estimate the overall effect size using random-effects meta-analyses. The overall results of nine trials with 641 participants, revealed that folic acid supplementation did not significantly change memory score compared to placebo (SMD: 0.12; 95% CI: -0.17, 0.40, p= 0.418; I2= 62.6%). However, subgroup analyses showed that supplementation with folic acid had favorable effects on memory levels considering the following conditions: 1) doses lower than 1 mg/day, 2) treatment lasting more than 6 months, 3) conducted in eastern countries, and 4) in participants equal to or older than 70 years old. The dose-response analysis suggested a significant favorable effect on memory status at doses of 6-11 mg/d and a significant decline at doses of 17-20 mg/d. Although we did not find a significant effect of folic acid supplementation on memory, there were some suggestions of beneficial effects in the subgroup analyses.